2017
DOI: 10.1111/jam.13397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochanin A on corn grain (Zea mays) fermentation by bovine rumen amylolytic bacteria

Abstract: BCA could serve as an effective mitigation strategy for rumen acidosis. Future research is needed to evaluate the effect of BCA on mitigating rumen acidosis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 61 publications
3
32
0
1
Order By: Relevance
“…The results of this study are consistent with a previous study that reported improvements in fibre digestibility with starch challenge when BCA treatment was added ex vivo (Harlow et al . ). These findings were primarily attributed to BCA addition ameliorating suspension pH decline and consequently increasing the viable number of cellulolytic bacteria.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of this study are consistent with a previous study that reported improvements in fibre digestibility with starch challenge when BCA treatment was added ex vivo (Harlow et al . ). These findings were primarily attributed to BCA addition ameliorating suspension pH decline and consequently increasing the viable number of cellulolytic bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…; Harlow et al . ). Many native rumen cellulolytic bacteria have the capacity for allelopathic competition via the production of bacteriocins or other antimicrobial molecules (Odenyo et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations